Implementation of a medication adherence program in senior public housing facilities utilizing pharmacists and health educators - Kimberly Pounds; Dominique Guinn; Ivy O Poon; Aisha Morris Moultry (Archives of Community Medicine and Public Health - Peertechz Publications, 2020)
Background: Hypertension and diabetes disproportionately impact people of color when compared to majority populations. Medication adherence among seniors with chronic diseases has been suboptimal with the estimation that only half of those taking antihypertensives are adherent. Therefore, the purpose of The Managing Your Medications (MY Rx) program was to evaluate the effectiveness of evidence-based practices used to improve rates of medication adherence through information dissemination among diabetic and hypertensive African American, Asian American, and Hispanic residents housed in senior public housing facilities in the Greater Houston Area. The program comprised an 8-week intervention with individual and group components with small incentives provided throughout the program. Individual components included one home visit and telephone consultations conducted by pharmacists. Health educators provided two group education sessions on lifestyle modifications.  Result: Qualitative analysis of focus group discussions revealed participant satisfaction with the MY Rx program and willingness to change after participation in the program.  Conclusion: The Rx program showed the potential effectiveness of an innovative strategy in medication counseling using interdisciplinary pharmacists and health educators to promote health. It demonstrated the importance of using the patient-centered care framework in designing a community intervention program.